PENGARUH CURRENT RATIO, TOTAL ASSETS TURNOVER, DAN NET PROFIT MARGIN, TERHADAP RETURN ON ASSETS - Nur Anita Chandra Putry; Teguh Erawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This study was conducted to examine the eff ect of variable current ratio (CR), TotalmAssets Turnover (TATO), and net profit margin (NPM) of the Return on Assets (ROA ) in themcompanies list ed in Indonesia Stock Exchange (IDX) 2009-2011. The sampling techniquenused is purposive sampling criteria companies listed in indonesia Stock Exchange (IDX) 20092011. Obtained a total sample of 25 companies of the 133 companies listed o n the Indonesia Stock Exchange (IDX) with a quantitative approach. The analysis technique used is mult iple regressions with SPSS tools. Based on the results of the analysis indicate th at the variable Current Ratio ( CR) , Total Assets Turnover (TATO) , and net profit margin (NPM) simulate proved significant effect on Return on Assets (ROA) . Predictive ability of these three variables on Return on Assets (ROA) shows the independent variables can explain the variation in the dependent variable was 89.1 % and the rest is explained by other variables. While partially variable Total Assets Turnover (TATO) and Net Profit Margin (NPM ) significantly i nfluence the Return on Assets (ROA) . While variable Current Ratio (CR ) showed no significant effect on the results of the Return on Assets (ROA). Keywords : Current Ratio (CR), Total Assets Turnover (TATO), Net Profit Margin (NPM), and Return on Assets (ROA)